Characterization of projections of longitudinal muscle motor neurons in human colon - Brookes, Simon; Humenick, Adam; Chen, Nan; Lauder, Chris I; Wattchow, David A; Zagorodnyuk, Vladimir P; Dinning, Phil; Spencer, Nick J; Costa, Marcello (SPARC Portal, 2022)
DiI-retrograde tracing ex vivo plus immunohistochemistry to characterize longitudinal muscle motor neurons.
Characterisation of human colon longitudinal muscle motor neurons